Surfactant therapy for acute respiratory distress in infants - Corrado Moretti (Journal of Pediatric and Neonatal Individualized Medicine, 2014)
Acute respiratory distress syndrome (ARDS) remains the primary indication for admission to paediatric intensive care units and accounts for significant mortality, morbidity and resource utilization. Respiratory infections, in particular pneumonia and severe bronchiolitis, are the most common causes of respiratory failure requiring mechanical ventilation in infants and children. This paper reviews the pathophysiology of ARDS and the management of paediatric patients with acute lung injury. Data indicate that adoption of a lung protective ventilation with low tidal volumes and of an open-lung ventilation strategy, characterized by sufficient positive end-expiratory pressure (PEEP) to avoid atelectasis, provides the greatest likelihood of survival and minimizes lung injury. The relative benefits of strategies such as high frequency oscillatory ventilation (HFOV), inhaled nitric oxide (iNO), recruiting manoeuvres and prone position are also considered.